Determining the Relevant Law in Countries with Multiple Legislation - a Comparative Study - Hassan, Media Dawoud (Journal of Legal and Political Studies, 2017)
The issue of determining the relevant law in states having multiple legislations is one of specific doctrinal question, because it relate to how to solve the problems of multiplicity of legislations that almost of country around the world have the same question. The multiplicity of legislations means the existing – or coexisting- of different legislations in one country. This multiplicity would be multi-ethnic legislations or different area legislations. In the multi-ethnic and multi-sectarians and nationals countries which are the result of different religion and faith, as is the case in Egypt, Iraq and other countries. The different area legislation is consist in countries which have different regions and states, so that each region has own specific legislation for example in the United States of America, Switzerland and Iraq. The consequence of this multi-access is an internal probable conflict between different nationals legislations. Although this internal conflict is a conflict between the legislations belong to one and same sovereign state. Iraq had entered a new phase, in all political, economic and social fields, having been changed after the fall of the Iraqi former regime, particularly after the issuance of the permanent Iraqi Constitution of 2005, which contains new principles and rules. The new Constitution admits the protection of religious, sectarian and ethnic minority rights in all parts of Iraq. This country became a federal state under which the Iraqi regions have the choice to act different laws or modify the existing Iraqi laws which do not fall within the exclusive powers of the federal government law. In this research, it has been showed that the Iraqi legislature has taken multi-ethnical or multiculturalism and multi regional legislation, in the base of which we make recommendations and suggestions to the Iraqi authorities in order to modify the legal text which contains legal multiplicity problem. In this field, we have presented legal texts that can be used to make the Iraqi reference t
Keywords: multiplicity of legislations; Internal conflicts; sovereign; consequence